Productivity imperative: wealth and poverty in the global economy - "Farrell, Diana. (ed.)" (Boston, 2006)
What factor most influences whether an economy will flourish or sink into poverty? Productivity. In this volume, experts examine the impact of productivity on a nation's economic well being and identify barriers to productivity based on analyses of industries from around the world.
Keywords: Productivity